Unravelling bad feelings, weaving trans care: : Kacen Callender’s Felix ever after - González-Díaz, Isabel (International Journal of English Studies, 2025)
This article explores the mixed and distressing feelings represented in Kacen Callender’s 2020 young adult novel Felix ever after, drawing on affect theories to highlight the potential that resignifying negative feelings can have for transgender youth. Along with reflecting on the transformative force of assertively managing bad feelings like anger or fear, the article analyses how the novel underscores the empowering effects that finding resilient care webs can have for young transgender individuals, particularly when confronting transphobia and questioning their identity.